PENGEMBANGAN MEDIA KARIER BERBASIS INSTAGRAM TERHADAP PILIHAN KARIER SISWA SMP TINGKAT IX - Inggriana, Ririn Nuri; Fatimah, Siti; Irmayanti, Rima (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
One of the services of Counseling Guidance is in the career field. The purpose of this study is to develop an Instagram-based career media for the career choices of junior high school students at level IX. . The subjects in this study were 35 grade IX students and 3 validator experts to test the feasibility of Instagram media. This study uses the R&D (Research and Development) method which is limited to 7 stages. The data analysis used is a feasibility test to determine the feasibility of Instagram to be used for students' career choices and a t-test used to determine the effectiveness of Instagram on students' career choices. Based on the results of the product feasibility test expert, it was stated that Instagram was in the "very feasible" category to be used as a medium for implementing guidance and counseling services with a percentage score of 80% from material experts, 94% from media experts, and 93% from expert practitioners (teachers). guidance and counseling). In addition, the test results on the student response questionnaire obtained a good percentage score of 93%. Based on the results that have been described, Instagram can be used as a medium for implementing guidance and counseling services in schools to help guidance and counseling teachers when providing services. Seeing the results of the effectiveness test on students' career choices also had significant results 0.00 < 0.05, which means that through Instagram media, students' career choices were found to increase after giving Instagram media.